PEMANFAATAN SUMBER DAYA ALAM DAN PELESTARIAN LINGKUNGAN HIDUP - Kunarto Kunarto (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2019)
In the perspective of environmental law, welfare which is the political goal of national law is not enough to be based only on the rule of law and democracy, but must also be based on the principles of the utilization of natural resources and environmental management. The principle must be a direction and policy making in the implementation of development, otherwise the welfare achieved will not last long, because Natural Resources as one of the elements of development capital cannot be functioned sustainable. Based on these arguments, conceptually the concept of implementing natural resource utilization and environmental management is the most important thing in national development that has been outlined in the legal policies set by the state or government to achieve the goals and objectives of environmental management. The goals and objectives are so that the environment is not damaged or polluted and maintained its function is preserved to preserve the carrying capacity and environmental capacity in order to achieve national development goals. If this function is not carried out properly, then the environment will be damaged or polluted, natural resources will be increasingly depleted, which in turn people's welfare which is one of the country's goals will not be achieved and sustainable.